Persistence : contemporary readings - Haslanger, Sally Anne; Kurtz, Roxanne Marie (MIT readers in contemporary philosophy., 2006)
Influential accounts of persistence⁰́₄how ordinary objects persist through time⁰́₄examine the perdurantist, exdurantist, and endurantist approaches and provide an overview of the topic.